Revolutionizing bone healing: the role of 3D models - Raffaella De Pace; Maria Rosa Iaquinta; Assia Benkhalqui; Antonio D’Agostino; Lorenzo Trevisiol; Riccardo Nocini; Chiara Mazziotta; John Charles Rotondo; Ilaria Bononi; Mauro Tognon; Fernanda Martini; Elisa Mazzoni (Cell Regeneration)
Abstract The increasing incidence of bone diseases has driven research towards Bone Tissue Engineering (BTE), an innovative discipline that uses biomaterials to develop three-dimensional (3D) scaffolds capable of mimicking the natural environment of bone tissue. Traditional approaches relying on two-dimensional (2D) models have exhibited significant limitations in simulating cellular interactions and the complexity of the bone microenvironment. In response to these challenges, 3D models such as organoids and cellular spheroids have emerged as effective tools for studying bone regeneration. Adult mesenchymal stem cells have proven crucial in this context, as they can differentiate into osteoblasts and contribute to bone tissue repair. Furthermore, the integration of composite biomaterials has shown substantial potential in enhancing bone healing. Advanced technologies like microfluidics offer additional opportunities to create controlled environments for cell culture, facilitating more detailed studies on bone regeneration. These advancements represent a fundamental step forward in the treatment of bone pathologies and the promotion of skeletal health. In this review, we report on the evolution of in vitro culture models applied to the study of bone healing/regrowth, starting from 2 to 3D cultures and microfluids. The different methodologies of in vitro model generation, cells and biomaterials are presented and discussed.